(3QSGdI Edi GdCSQI (B/s - (3GdedG, eMeO Ydjs 1972-; (3GdUhGa, eMeO TQja s 1970- ((3OeTb (B- (3ShQjG (B:s (3OGQ GdYUeGA ,s (3OGQ QhGO GdeLO ,s, 2020)
(3jJfGhd cJGH (B((3QSGdI Edi GdCSQI(B) (3hGdPj bGeg HJCdjag (B((3eMeO Ydj GdedG(B) (3aj MhGdj (B(129) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdCSQI aj GdESdGe eSJYQVG GdeMJhjGJ GdJGdjI (B: (3dbO fXQ GdESdGe Edi GdCSQI fXQI NGUI(B... (3hgPg GdfXQI eHfjI Ydi Cf GdCSQI gj CSGS GdeLJeY(B. (3bGd Gddg JYGdi (B: ((3jGCjgG GdPjf BefhG bhG CfaSce hCgdjce fGQG hbhOgG GdfGS hGdMLGQI YdjgG edGFcI ZdGX TOGO dG jYUhf Gddg eG CeQge hjaYdhf eG jDeQhf(B(6))... ((3ShQI GdJMQje(B) (3hjHbi GdSDGd GdCge GdPj jHjf dfG gOa gPG GdcJGH (B: (3cja fHfj CSQI UGdMI Jchf dHfI bhjI aj HfGA eLJeY bhj UGdM eJeSc HGdcJGH hGdSfI ? (B!... (3hGdLhGH SJLOhfg Ef TGA Gddg JYGdi aj gPg GdQSGdI(B.s
Keywords: (3GdCSQI aj GdESdGes; (3HQ GdhGdOjfs